VELVET: an enclosure vegetation system to measure BVOC emission fingerprints in temperate and tropical climates - Rocco, Manon; Brugere, Etienne; Magand, Olivier; Borbon, Agnes; Colomb, Aurelie; Bouvier, Laetitia; Baray, Jean-Luc; Duflot, Valentin; Ribeiro, Mickael; Picard, David; Metzger, Jean-Marc; Stamenoff, Pierre; et al. (Frontiers in Environmental Science, 2024)
The VELVET chamber, utilizing the vegetation enclosure technique, was used to measure biogenic volatile organic compound emissions from representative plant leaves in temperate and tropical climates. This study demonstrates the instrument's capability, among the various measurements conducted in other studies using the vegetation enclosure technique, in qualifying and quantifying VOCs emissions from different tree species. The measurements were performed by TENAX tubes sampling and GC/MS analysis. The use of PTR-ToF-MS for temperate species allows us to perform flux measurements in the chamber of Norway spruce (Picea abies), European beech (Fagus sylvatica) and common hazel tree (Corylus avellana) in the Puy de Dôme region (France). We found that all species are monoterpenes emitters (on average 1.52 ± 0.29 ng m -2 s -1 ) and more particularly sesquiterpenes emitters for C. avellana (7.49 ± 0.70 ng m -2 s -1 ). In the tropical region of Réunion Island (France), comprehensive measurements were conducted across three distinct vegetation types, on 10 of the most representative species, native and exotic to the island. The study revealed that emissions from these species were influenced by spatial variability, their environment and the type of the forest (cloud forest, high and low altitude forests). Notably, the research marked a groundbreaking achievement by capturing emissions from endemic species on the island for the first time. The collected data will be added to the biogenic emission inventory of the island, thereby enhancing model simulations by incorporating these new measurements.